Pengaruh Pembayaran melalui Metode Paylater Terhadap Minat Belanja Mahasiswa: (Studi Kasus:Universitas Islam Negri Sultan maulana Hasanuddin banten) - Desty Anggraini (Asosiasi Riset Ekonomi dan Akuntansi Indonesia, 2024)
The emergence of new payment methods such as Paylater makes shopping easier and increases consumers' shopping interest. This research aims to find out how much influence the paylater payment method has on students' shopping interest. The method used in this research is a quantitative method. Based on the results of the T Test and F Test, the variable